2012
DOI: 10.1371/journal.pone.0052911
|View full text |Cite
|
Sign up to set email alerts
|

β1-Adrenoceptor Autoantibodies from DCM Patients Enhance the Proliferation of T Lymphocytes through the β1-AR/cAMP/PKA and p38 MAPK Pathways

Abstract: BackgroundAutoantibodies against the second extracellular loop of the β1-adrenergic receptor (β1-AA) not only contribute to increased susceptibility to heart failure, but also play a causative role in myocardial remodeling through their sympathomimetic-like effects that are induced upon binding to the β1-adrenergic receptor. However, their role in the function of T lymphocytes has never been previously investigated. Our present study was designed to determine whether β1-AA isolated from the sera of dilated car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…We previously demonstrated that β 1 -AA was likely to promote proliferation in T lymphocytes through p38MAPK25. Here we found that β 1 -AA increased the level of phosphorylated p38MAPK and ERK1/2 in cardiac fibroblast, which is similar to previous study.…”
Section: Discussionsupporting
confidence: 91%
“…We previously demonstrated that β 1 -AA was likely to promote proliferation in T lymphocytes through p38MAPK25. Here we found that β 1 -AA increased the level of phosphorylated p38MAPK and ERK1/2 in cardiac fibroblast, which is similar to previous study.…”
Section: Discussionsupporting
confidence: 91%
“…Further studies indicated that β 1 -AAbs displayed an analogous agonist effect mediated by β 1 -AR [4]. This process appears to contribute to heart failure and dilated cardiomyopathy [5,6]. We have shown that β 1 -AAbs are involved in ventricular arrhythmia formation in guinea pigs through activation of β 1 -AR.…”
Section: Introductionmentioning
confidence: 73%
“…A previous report demonstrated that β 1 AR-AAbs enhanced proliferation of rat CD3+ T lymphocytes in vitro, which was blocked by the selective β1AR antagonist metoprolol (42). β 1 AR-AAbs also inhibited the secretion of interferon-γ while promoting an increase in interleukin-4 levels.…”
Section: Discussionmentioning
confidence: 98%